Cost-effectiveness analysis of the introduction of the human papillomavirus vaccine in Honduras. (7th May 2015) - Aguilar, Ida Berenice Molina; Mendoza, Lourdes Otilia; García, Odalys; Díaz, Iris; Figueroa, Jacqueline; Duarte, Rosa María; Perdomo, Gabriel; Garcia, Ana Gabriela Felix; Janusz, Cara Bess
Highlights: Honduras EPI and cervical cancer program analyzed the costs, health impact and cost-effectiveness of HPV vaccine. HPV vaccination is likely cost-effective for Honduras. Affordability is a concern because Honduras is graduating from Gavi support. Abstract: Background: Cervical cancer is the leading cause of cancer deaths in Honduras. With the availability of a vaccine to prevent human papillomavirus (HPV), the causative agent for cervical cancer, the Honduran Secretary of Health undertook a cost-effectiveness analysis of introducing the HPV vaccine to support their national decision-making process. Methods: A national multidisciplinary team conducted this analysis with the CERVIVAC model, developed by the London School of Hygiene and Tropical Medicine in collaboration with the Pan American Health Organization's ProVac Initiative. The cumulative costs and health benefits of introducing the HPV vaccine were assessed over the lifetime of one single cohort of 11-year-old girls. We assumed a three-dose series with 95% vaccination coverage of the cohort using a mixture of school-based and facility-based delivery. To estimate national cervical cancer cases and deaths, we used United Nations demographic projections and GLOBOCAN estimates based on registry data from El Salvador, Guatemala, and Nicaragua. Based on estimates from the World Health Organization (WHO) and the Division of Intensified Cooperation with Countries (ICO), we assumed that 70% of cervical cancer would be due to vaccine types HPV16 and HPV18. We used a vaccine dose price of US 13.45 and evidence from the scientific literature to estimate vaccine effectiveness. National information was used to estimate health service utilization and costs of cervical cancer treatment. All costs and health benefits were discounted at 3%. Results: Upon fully vaccinating 86, 906 11-year old girls, 2250 (undiscounted) cervical cancer cases and 1336 (undiscounted) deaths would be prevented over the lifetime of the cohort. After discounting future health benefits at 3% per year, the equivalent cases and deaths prevented were 421 and 170. HPV vaccination is estimated to cost around US 5 million per vaccinated cohort, but this would be offset by around US 1 million in avoided costs borne by the government to treat cervical cancer. Furthermore, 4349 discounted disability adjusted life years (DALYs) could be avoided at a cost of US 926 per DALY avoided, making HPV vaccination in Honduras a highly cost-effective intervention. Discussion: The net cost of HPV vaccination per DALY avoided is less than the WHO threshold for cost-effectiveness. However, at a cost of around US 5 million per vaccinated cohort, an important element to consider in this discussion is the budgetary implications that the introduction of the HPV vaccine would cause for the country. Conclusions: When comparing the costs and benefits of HPV vaccine introduction in Honduras, it is clear that this intervention would be highly cost-effective and that the intervention would greatly reduce cervical cancer disease. For these reasons, it is in the country's best interest to explore financing opportunities that could support the vaccine's introduction.